Refraining from culture-related discussions in English as a foreign language classrooms: lessons from negative cases - Lavrenteva, Evgenia; Orland-Barak, Lily (Frontiers in Education, 2024)
This study examined the factors that determined English as a Foreign Language (EFL) teacher decisions to refrain extending the use of culture-related classroom discussions.The negative case analysis reported in the study enriched our understanding of the obstacles and impediments anticipated by teachers in the process of bridging the gap between their intended goals of language-and-culture-teaching and actual classroom practices. Specifically, we focused on the episodes in which teachers decided against holding specific culture-related discussions, to better understand the reasons for limited inclusion of diverse cultural content. A thematic analysis of teacher interviews (N = 30) interpreted through the lens of Ajzen's Theory of Planned Behaviour, revealed that Israeli EFL teachers' decisions to refrain from culture-related classroom discussions were influenced by their personal norms and attitudes, perceptions of their roles as teachers, social conventions and expectations of various school stakeholders. Specifically, we found that the major barriers to conducting culturally-related classroom conversations in the Arab sector had to do with the values endorsed by the school culture, with teachers' tendency to avoid taboo topics in their teaching due to concerns about how students would react or become alienated. For immigrant teachers, personal norms and perceptions of control operated as key factors in their decisions to avoid sensitive issues.Majority teachers cited negative attitudes, moral panics, school culture and perceptions of control as principal reasons for avoiding controversial topics. The emergent patterns are discussed as embedded in the cultural and social norms with possible implications for teaching in the multicultural classroom.